Cross-scale interaction of host tree size and climatic water deficit governs bark beetle-induced tree mortality - Koontz, Michael J.; Latimer, Andrew M.; Mortenson, Leif A.; Fettig, Christopher J.; North, Malcolm P. (Nature communications, 2021)
The recent Californian hot drought (2012–2016) precipitated unprecedented ponderosa pine ( Pinus ponderosa ) mortality, largely attributable to the western pine beetle ( Dendroctonus brevicomis ; WPB). Broad-scale climate conditions can directly shape tree mortality patterns, but mortality rates respond non-linearly to climate when local-scale forest characteristics influence the behavior of tree-killing bark beetles (e.g., WPB). To test for these cross-scale interactions, we conduct aerial drone surveys at 32 sites along a gradient of climatic water deficit (CWD) spanning 350 km of latitude and 1000 m of elevation in WPB-impacted Sierra Nevada forests. We map, measure, and classify over 450,000 trees within 9 km 2 , validating measurements with coincident field plots. We find greater size, proportion, and density of ponderosa pine (the WPB host) increase host mortality rates, as does greater CWD. Critically, we find a CWD/host size interaction such that larger trees amplify host mortality rates in hot/dry sites. Management strategies for climate change adaptation should consider how bark beetle disturbances can depend on cross-scale interactions, which challenge our ability to predict and understand patterns of tree mortality. The 2012–2016 drought and western pine beetle outbreaks caused unprecedented mortality of ponderosa pine in the Sierra Nevada, California. Here, the authors analyse drone-based data from almost half a million trees and find an interaction between host size and climatic water deficit, with higher mortality for large trees in dry, warm conditions but not in cooler or wetter conditions.